Physiological potential of cowpea seeds produced in two regions of the State of Ceará - Teófilo, Elizita (2008)
Physiological evaluation of the quality of seeds has been basic in programs of quality control. The present work aimed to evaluate the physiological quality of cowpea seeds of the cultivars Aparecido, Epace-10, BRS Marataoã, Patativa, Paulistinha, Pingo de Ouro, BRS Rouxinol, Sempre Verde e Setentão, produced in two different regions of the State of Ceará. The seeds were produced in Pentecoste and Quixadá during the year of 2006. The seeds were tested for germination, first germination counting, seedling emergency, velocity of emergency index, and dry weight of the aerial part. Seed produced in Pentecoste perform better compared with those produced in Quixadá. The cultivars Aparecido and BRS Marataoã had better quality in Pentecost and Quixadá. The cultivars Epace-10, Patativa and BRS Rouxinol showed physiological lower quality, in the two places.